Analisis Kelayakan Nasabah Dalam Pembiayaan KPR iB Griya Barokah Pada Bank Jatim Syariah Cabang Sidoarjo - Herlina Rahma Yanti; Putri Ayu Fitria Sari; Wulan Alyu Nabilla; Muhammad Iqbal Surya Pratikto (STIKes Ibnu Sina Ajibarang, 2024)
The aim of this research is to determine the method used by Bank Jatim Syariah Sidoarjo Branch in analyzing the suitability of iB Barokah home ownership credit (KPR) customers. By using interview techniques, a qualitative research approach was used. Based on research findings, it is known that Bank Jatim Syariah Sidoarjo Branch applies the 5C principles by paying special attention to collateral, capacity and character. The sustainability of financing is greatly influenced by these three factors. Meanwhile, in the conditional point of economy and capital, it is only a supporting factor because it is considered not to have a significant impact on the financing process